An Analysis of Teachers Educational Role in Developing Religious Character Among Lower Grade Students - Kirana Primandini; Ali Sunarso (Jurnal Teknologi Pendidikan)
Religious character is a fundamental value that must be instilled in students as the foundation for a nation's progress. One of the most crucial aspects of developing religious character is the role of teachers. This study aims to analyze and identify the role of teachers and the indicators of their success in shaping the religious character of lower-grade students. This research employs a descriptive qualitative approach, with research subjects including religious studies teachers, first-grade teachers, second-grade teachers, and third-grade teachers. The sampling technique used is purposive sampling. Data were collected through observation, interviews, and documentation. To ensure data validity, this study applies triangulation techniques. The data analysis process consists of data collection, data reduction, data presentation, and conclusion drawing. The findings of this study indicate that the role of teachers in developing the religious character of lower-grade students encompasses three main aspects: as educators, mentors, and guides, by implementing a behavioristic-based learning strategy. As educators, teachers encourage students to develop positive habits. As mentors, they provide guidance in spiritual and religious aspects, such as teaching the correct way to perform ablution (wudhu), training students in the call to prayer (adhan), guiding them in performing prayers (salat), assisting in the recitation of Asmaul Husna, and helping students properly recite Juz Amma. Meanwhile, as guides, teachers play a crucial role in instilling moral values such as honesty, discipline, and tolerance. The indicators of success are reflected in positive changes observed in students, such as increased honesty, discipline, tolerance, religious practices, and improved ability to memorize short surahs.